Drug and alcohol positivity of traumatically injured patients related to COVID-19 stay-at-home orders. (3rd September 2021) - Young, Kirsten N.; Yeates, Eric O.; Grigorian, Areg; Schellenberg, Morgan; Owattanapanich, Natthida; Barmparas, Galinos; Margulies, Daniel; Juillard, Catherine; Garber, Kent; Cryer, Henry; Tillou, Areti; Burruss, Sigrid; et al.
ABSTRACT: Background : COVID-19 related stay-at-home (SAH) orders created many economic and social stressors, possibly increasing the risk of drug/alcohol abuse in the community and trauma population. Objectives : Describe changes in alcohol/drug use in traumatically injured patients after SAH orders in California and evaluate demographic or injury pattern changes in alcohol or drug-positive patients. Methods : A retrospective analysis of 11 trauma centers in Southern California (1/1/2020-6/30/2020) was performed. Blood alcohol concentration, urine toxicology results, demographics, and injury characteristics were collected. Patients were grouped based on injury date – before SAH (PRE-SAH), immediately after SAH (POST-SAH), and a historical comparison (3/19/2019-6/30/2019) (CONTROL) – and compared in separate analyses. Groups were compared using chi-square tests for categorical variables and Mann-Whitney U tests for continuous variables. Results : 20, 448 trauma patients (13, 634 male, 6, 814 female) were identified across three time-periods. The POST-SAH group had higher rates of any drug (26.2% vs. 21.6% and 24.7%, OR = 1.26 and 1.08, p < .001 and p = .035), amphetamine (10.4% vs. 7.5% and 9.3%, OR = 1.43 and 1.14, p < .001 and p = .023), tetrahydrocannabinol (THC) (13.8% vs. 11.0% and 11.4%, OR = 1.30 and 1.25, p < .001 and p < .001), and 3, 4-methylenedioxy methamphetamine (MDMA) (0.8% vs. 0.4% and 0.2%, OR = 2.02 and 4.97, p = .003 and p < .001) positivity compared to PRE-SAH and CONTROL groups. Alcohol concentration and positivity were similar between groups ( p > .05). Conclusion : This Southern California multicenter study demonstrated increased amphetamine, MDMA, and THC positivity in trauma patients after SAH, but no difference in alcohol positivity or blood concentration. Drug prevention strategies should continue to be adapted within and outside of hospitals during a pandemic.